Ranking of companies according to the indicators of corporate social responsibility based on SWARA and ARAS methods - Karabasevic, Darjan; Paunkovic, Jane; Stanujkic, Dragisa (Serbian Journal of Management, 2015)
Corporate sector and companies have recognized the importance of implementation of strategy of corporate social responsibility in order to increase the company's image and responsibility towards society and the communities where they operate. Multinational companies in their everyday activities and operations pay more attention to sustainable models of corporate social responsibility. The focus of this paper is to identify the indicators of corporate social responsibility and to rank companies according to the indicators. Proposed framework for evaluation and ranking is based on the SWARA and the ARAS methods. The usability and efficiency of the proposed framework is shown on an illustrative example.